PEDAGOGICAL CONDITIONS OF EFFICIENCY INCREASE AND PROFESSIONAL EDUCATION OF STUDENTS WHILE STUDENTS’ UNION ORGANIZATION - Sharshov, I.A.; Borzykh, I.N. (Tambov University Review. Series: Humanities, 2016)
The necessity to define pedagogical conditions of improvement of the effectiveness of professional education of youth during organization of students’ self-governance (OSSG) in the institute of higher education from the triune position: basing on theoretical-methodological analysis of the studied notions’ essence basing on the marked pedagogical contradictions of professional education while students’ self-governance in the institute of higher education and basing on the disadvantages’ analysis of this project in practice. The state stage of the experiment is presented. It characterizes primary level of the formation of the studied notion according to the marked criteria and indices, taking into consideration the characteristic features of students’ professional education. The methods of research are characterized. Special methods of diagnostics of the developed criteria diagnostics and also the procedure of defining the level of formedness of indices and criteria of the phenomenon researched and also the level of formedness of professional education in whole are studied. The drawbacks of formation of every index partially and the possible reasons of their appearance are analyzed. The data received by empiricism confirm our theoretical conclusions about the necessity of professional education of students - the future public employees. An important factor is the participation of students in self-governance, while this process the marked professional-personal qualities will be formed. The total pedagogical conditions of professional education of future public officers while students’ self-governance as total pedagogical conditions, promoting the increase of efficiency of this process in the institute of higher education: organization of subjects’ orientation on professional education in the process of participation in students’ self-governance; activation and development of reflection mechanisms, professional self-identification according to the requirements of future professional activity and conditions of students’ self-governance; the increase of independent types of activity in students’ self-governance, appropriate for future professional duties; development of subject-subject relations in students’ self-governance as a basis for professional relations, providing the necessary level of personal and business communication, creation within the framework of students’ self-governance of professional community model for learning patriotic values, ethic rules and state service traditions.